Construction of a telomerase-immortalized porcine tracheal epithelial cell model for swine-origin mycoplasma infection - Xing XIE; Fei HAO; Hai-yan WANG; Mao-da PANG; Yuan GAN; Bei-bei LIU; Lei ZHANG; Yan-na WEI; Rong CHEN; Zhen-zhen ZHANG; Wen-bin BAO; Yun BAI; et al. (Journal of Integrative Agriculture, 2022)
Primary porcine tracheal epithelial cells (PTECs) are an appropriate model for studying the molecular mechanism of various porcine respiratory diseases, including swine-origin mycoplasmas, which are isolated from respiratory tract of pigs and mainly found on the mucosal surface surrounding swine trachea. However, the short proliferation ability of primary PTECs greatly limits their lifespan. In this study, primary PTECs were carefully isolated and cultured, and immortal PTECs were constructed by transfecting primary PTECs with the recombinant constructed plasmid pEGFP-hTERT containing human telomerase reverse transcriptase (hTERT). Immortal PTECs (hTERT-PTECs) maintained both the morphological and functional characteristics of primary PTECs, as indicated by the expression of cytokeratin 18, cell-cycle analysis, proliferation assay, Western blotting, telomerase activity assay, karyotype analysis and quantitative RT-PCR. Compared to primary PTECs, hTERT-PTECs had an extended replicative lifespan, higher telomerase activity, and enhanced proliferative activity. In addition, this cell line resulted in a lack of transformed and grown tumors in nude mice, suggesting that it could be safely applied in further studies. Moreover, hTERT-PTECs were vulnerable to all swine-origin mycoplasmas through quantitative analysis as indicated by 50% color changing unit (CCU50) calculation, and no significant differences of adhesion ability between primary and immortal PTECs were observed. For the representative swine mycoplasma Mycoplasma hyopneumoniae (Mhp), except for DNA copies quantitative real-time PCR assay, indirect immunofluorescence assay and Western blotting analysis also depicted that hTERT-PTECs was able to adhere to different Mhp strains of different virulence. In summary, like primary PTECs, hTERT-PTECs could be widely used as an adhesion cell model for swine-origin mycoplasmas and in infection studies of various porcine respiratory pathogens.